Mathematical Thinking Styles-The Advantage of Analytic Thinkers When Learning Mathematics - Jaime Huincahue; Rita Borromeo-Ferri; Pamela Reyes-Santander; Viviana Garrido-Véliz (MDPI AG, 2021)
School is a space where learning mathematics should be accompanied by the student's preferences; however, its valuation in the classroom is not necessarily the same. From a quantitative approach, we ask from the mathematical thinking styles (MTS) theory about the correlations between preferences of certain MTS and mathematical performance. For this, a valid test instrument and a sample of 275 16-year-old Chilean students were used to gain insight into their preferences, beliefs and emotions when solving mathematical tasks and when learning mathematics. The results show, among other things, a clear positive correlation between mathematical performance and analytical thinking style, and also evidence the correlation between self-efficacy, analytical thinking and grades. It is concluded that students who prefer the analytical style are more advantageous in school, since the evaluation processes have a higher valuation of analytic mathematical thinking.